THE NEUROPROTECTIVE EFFECTS OF INHALED HYPERICUM SCABRUM L. (HYPERICACEAE) ESSENTIAL OIL AGAINST SCOPOLAMINE-INDUCED ALZHEIMER'S TYPE DEMENTIA - SUR, TARIQ HASSAN MOHAMMED (Fırat Üniveristesi, 2017)
Alzheimer hastalığı şuana kadar bir tedavisi bulunmayan nörodejeneratif bir hastalıktır bu kalşmada. Hypericum scabrum özellikle Anadolu'da yıllardan beri geleneksel tıpta kullanılmaktadır. Hypericum scabrum uçucu yağı GC-MS ile analiz edilmiştir. Hypericum scabrum essential oil % 1and Hypericum scabrum essential oil %3 grupları 21 gün boyunca uçucu yağına maruz kalmışlardır. Uçucu yağda alfa-pinen (%51.3) major bileşen olarak bulunmuştur. Uçucu yağ solunumu Y-labirentinde spontan değişim yüzdesinde artışa, radial kol labirentinde işleyen hafıza hatalarında ve referans hafıza hatalarında düşüşe, yükseltilmiş artı labirentinde açık kola giriş sayılarında ve geçiş sayılarında artışa, zorunlu yüzme testinde yüzme süresinde artışa, hareketsizlik süresinde ise düşüşe yol açmıştır. Yalnız skopolamin uygulanan gruba göre ratların hipokampüs ve amigdala beyin dokularında GPX (glutathione peroxidase), GSH (glutathione) ve SOD (superoxide dismutase) seviyelerinde artış, MDA (malondialdehyde) seviyesinde ise düşüş görülmüştür. Çalışmamız H. scabrum uçucu yağının amigdala ve hipokampüsteki oksidatif stresi azaltarak skopolaminle oluşan hafıza geriliğini önlediğini ve anksiyete ve depresyonu azalttığını göstermiştir. Anahtar kelimeler: Alzheimer hastalığı, Hypericum scabrum, Anksiyete and Depresyon, Oksidatif stres

Alzheimer's disease is a neurodegenerative illness with no effective treats for now. In this study H. scabrum has been used in traditional medicine for several years, especially in Anatolia. H. scabrum essential oil was analyzed by GC-MS. Hypericum scabrum essential oil 1% and Hypericum scabrum essential oil 3% groups inhaled the oil for 21 continuous days. In the essential oil the ?-pinene (51.3 %) was found to be the major component. Inhalation of this oil caused to increase spontaneous alternations % in Y-maze, decreased working memory errors and reference memory errors in radial arm-maze, increased the number of open-arm entries and number of arm crossings in elevated plus-maze, also increased swimming time and decreased immobility time in forced swimming test. Elevation of GPX (glutathione peroxidase), GSH (glutathione) and SOD (superoxide dismutase), and reduction of MDA (malondialdehyde) levels in the homogenates of hippocampus and amygdala tissues of rat brains were reported in the essential oil treated rats compared to scopolamine alone-treated rats. Our study showed that, inhalation of H. scabrum essential oil prevents scopolamine-induced memory impairment, and reduces anxiety and depression by attenuation of the oxidative stress in the rat hippocampus and amygdala. Keywords: Alzheimer's disease, Hypericum scabrum, Anxiety and Depression, Oxidative stress.
Scopolamine ile oluşturulan lzheimer tipi demansa karşım Hypericum scabrum L. (Hypericaceae) uçucu yağı solunumunun sinir-koruyucu etkileri
Keywords: Biyoteknoloji; Biyoloji; Botanik